2004
DOI: 10.1002/ajpa.10429
|View full text |Cite
|
Sign up to set email alerts
|

New method for surname studies of ancient patrilineal population structures, and possible application to improvement of Y‐chromosome sampling

Abstract: Several studies showed that surnames are good markers to infer patrilineal genetic structures of populations, both on regional and microregional scales. As a case study, the spatial patterns of the 9,929 most common surnames of the Netherlands were analyzed by a clustering method called self-organizing maps (SOMs). The resulting clusters grouped surnames with a similar geographic distribution and origin. The analysis was shown to be in agreement with already known features of Dutch surnames, such as 1) the geo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
44
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 31 publications
0
44
0
2
Order By: Relevance
“…More recently and in the frame of molecular studies focused on the variability of the Y-chromosome, the study of surnames gained new prominence and has been advocated to design more careful sampling strategies (Boattini et al 2010;Manni et al 2005). Nowadays the technological constraints related to DNA typing are becoming negligible, thus allowing more energy for a meticulous collection of the samples.…”
Section: Ho Visto Un Lampo Illuminare Scene Del Futuro Gli Anni MI Dmentioning
confidence: 99%
See 3 more Smart Citations
“…More recently and in the frame of molecular studies focused on the variability of the Y-chromosome, the study of surnames gained new prominence and has been advocated to design more careful sampling strategies (Boattini et al 2010;Manni et al 2005). Nowadays the technological constraints related to DNA typing are becoming negligible, thus allowing more energy for a meticulous collection of the samples.…”
Section: Ho Visto Un Lampo Illuminare Scene Del Futuro Gli Anni MI Dmentioning
confidence: 99%
“…To overcome this limitation, Manni et al (2005) introduced a general surname method (General Method) providing a fast and efficient identification of those geographical areas that remained genetically closer to their past genetic makeup: in other words where immigration has been less intense. When studies about past DNA variability are undertaken, this method enables the design of a more efficient Y-chromosome sampling, because donors can be selected according to the geographic origin of their patrilineal ancestor (being such inference limited to the interval spanning from the present to the time of surname introduction).…”
Section: Ho Visto Un Lampo Illuminare Scene Del Futuro Gli Anni MI Dmentioning
confidence: 99%
See 2 more Smart Citations
“…4 It has even been shown that in the ideal case population substructure can be inferred only on the basis of detailed surname analyses. 5 Although this might be true in general, in isolated cases false paternity or in vitro fertilization by means of anonymous sperm donors disrupts the link between a particular surname and its corresponding Y-chromosomal genotype. Of course, also a perfectly legal marriage can introduce 'exotic' Y-chromosomes into a pedigree.…”
mentioning
confidence: 99%